Associations between postnatal weight gain, change in postnatal pulmonary function, formula feeding and early asthma - Turner, S.; Zhang, Guicheng; Young, S.; Cox, M.; Goldblatt, J.; Landau, L.; Le Souëf, P. (BMJ Group, 2008)
Background: A study was undertaken to examine factors that might influence lung function during infancy and to test the hypothesis that change in weight during infancy is negatively associated with change in lung function. Methods: Weight, length and maximal flow at functional residual capacity (V'maxFRC) were measured at ages 1 and 12 months. V'maxFRC was adjusted for length. Asthma symptoms and age at introduction of formula feeds were identified from questionnaires. Groups were dichotomised by V'maxFRC at 1 month and change in V'maxFRC. Results: 154 infants were assessed at ages 1 and 12 months. The change in V'maxFRC was inversely associated with change in weight (r = -0.18, r2 = 0.13, p<0.001). The group with lower V'maxFRC at 1 month and reduced change in V'maxFRC over infancy had the greatest weight gain (p = 0.003) and increased risk for asthma symptoms by 3 years (p = 0.017) but not afterwards. Exclusive breast feeding to 6 months was associated with a mean reduction in weight gain at age 12 months in comparison with earlier introduction of formula milk (mean difference 0.65 kg, p = 0.001), and was also associated with reduced asthma symptoms at 3 years (odds ratio 0.44, p = 0.043) but not at 6 or 11 years of age. Conclusions: Weight gain in infancy is inversely associated with change in lung function during infancy. Postnatal weight gain may be indirectly associated with early transient asthma symptoms via an influence on lung growth during infancy, and this is potentially modifiable by breast feeding. These associations could be relevant to the clinically recognised syndrome of the "fat happy wheezer".